1998
DOI: 10.1097/00007435-199809000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Subtyping of Treponema pallidum Subspecies pallidum

Abstract: This is the first molecular subtyping system that distinguishes among clinical isolates of T. pallidum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
195
2
15

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(222 citation statements)
references
References 21 publications
10
195
2
15
Order By: Relevance
“…Опубликованы данные о широком распространении двух субтипов ВИЧ-1 в Таиланде [88], преобладании субтипа А ви-руса иммунодефицита человека 1-го типа в популя-ции с высокой превалентностью ВИЧ в Северной Америке (Нью-Йорк) [89], о результатах изучения методами молекулярной эпидемиологии путей рас-пространения субтипов ВИЧ-1 B и Е [90], Chlamydia trachomatis [91], Treponema pallidum [92][93][94]. По мне-нию авторов проведенных исследований, примене-ние методов молекулярного типирования способ-ствует пониманию закономерностей распростране-ния генотипов возбудителя между регионами одной страны и странами мира, изучению биологических особенностей возбудителей, циркулирующих в раз-ных географических регионах, в том числе установ-лению возможной связи субтипов с вирулентно-стью, определению особенностей передачи инфек-ции между половыми партнерами.…”
Section: современные подходы к эпидемиологическому наблюдению над расunclassified
“…Опубликованы данные о широком распространении двух субтипов ВИЧ-1 в Таиланде [88], преобладании субтипа А ви-руса иммунодефицита человека 1-го типа в популя-ции с высокой превалентностью ВИЧ в Северной Америке (Нью-Йорк) [89], о результатах изучения методами молекулярной эпидемиологии путей рас-пространения субтипов ВИЧ-1 B и Е [90], Chlamydia trachomatis [91], Treponema pallidum [92][93][94]. По мне-нию авторов проведенных исследований, примене-ние методов молекулярного типирования способ-ствует пониманию закономерностей распростране-ния генотипов возбудителя между регионами одной страны и странами мира, изучению биологических особенностей возбудителей, циркулирующих в раз-ных географических регионах, в том числе установ-лению возможной связи субтипов с вирулентно-стью, определению особенностей передачи инфек-ции между половыми партнерами.…”
Section: современные подходы к эпидемиологическому наблюдению над расunclassified
“…In the Nichols genome, this insertion was found only in part of the treponemal population (Šmajs et al, 2002). With regard to the arp gene (Pillay et al, 1998), a variable number of tandem repetitions were found in the tested genomes. Based on amino acid variations, previously published papers (Harper et al, 2008b;Liu et al, 2007) classified the TPA and TPE Arp repeat motifs into 4 types (I, II, III, II/III), and the variability in repeat sequence types correlated with the sexual transmission strategy (Harper et al, 2008b).…”
Section: Whole Genome Fingerprintingmentioning
confidence: 99%
“…The Tpr proteins are heterogenous proteins considered as potential virulence factors involved in pathogenesis and/or immune evasion (Giacani et al, 2004;Gray et al, 2006), and in inducing an antibody response during treponemal infection (Centurion-Lara et al, 1999, 2000a, 2000b. Other differences between TPA and TPE involved a Mcp (methyl-accepting chemotaxis protein, TPE_0488), three treponemal antigens (TPE_0136; (Brinkman et al, 2008), the Tp92 -outer membrane protein (TPE_0326; Cameron et al, 2000), the Arp protein (TPE_0433, Pillay et al, 1998)) and an elongated RecQ protein (TPE_0103) (Čejková et al, unpublished results).…”
Section: Whole Genome Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is ample time to identify sexual contacts and treat them to interrupt the chain of transmission. To understand the patterns and dynamic of disease transmission, molecular typing methods are being developed (15). These typing schemes will be useful in the construction of accurate spread networks for the sexual transmission of disease and will be important tools for outbreak investigation and control.…”
Section: Syphilismentioning
confidence: 99%